Composite seed crystal and preparation method and application thereof

By preparing composite seed crystals and using the means of inducing destabilization of supersaturated solutions, the problem of difficulty in removing sulfate from high-concentration sulfate wastewater in the prior art is solved, and a high-efficiency, low-cost and environmentally friendly sulfate removal effect is achieved.

CN119551702APending Publication Date: 2025-03-04XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531305.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove sulfate from high concentration sulfate wastewater, and there are problems of high cost, toxicity and secondary pollution.

Method used

By preparing composite seeds, using seed support to support seeds, calcined, the composite seeds are obtained, and the sulfate and calcium ions present in the water are used to achieve efficient removal of sulfate based on the means of inducing destabilization and precipitation of supersaturated solutions.

Benefits of technology

It has achieved efficient removal of sulfate from water bodies, reduced process costs, no sludge production, no secondary pollution, and is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551702A_ABST
    Figure CN119551702A_ABST
Patent Text Reader

Abstract

The invention provides a composite seed crystal and a preparation method and application thereof. According to the composite seed crystal prepared by the preparation method provided by the invention, sites can be provided for attachment of sulfate radical precipitation, the reaction activation energy in the crystallization process of the sulfate radical precipitation is effectively reduced, and the reaction surface area is increased; finally, the technical effect of efficiently removing the sulfate radicals in the water body can be achieved, the process cost is reduced, no sludge is generated, no secondary pollution is generated, and the method is suitable for industrial popularization of wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a composite crystal seed and a preparation method and application thereof. Background Art

[0002] High-concentration sulfate wastewater mainly comes from two types of industrial wastewater: one is mining wastewater containing sulfate; the other is wastewater discharged from fermentation, pharmaceutical and light industries. The sulfate concentration in these wastewaters exceeds 2000mg / L, and even reaches 5000mg / L. If it cannot be effectively removed, on the one hand, it will affect the biochemical treatment effect of the wastewater, and on the other hand, the sulfate discharged with the wastewater will have a harmful impact on the environment, especially causing land salinization.

[0003] At present, the technical methods for removing sulfate radicals mainly include BaCl2 method, CaCl2 method, freezing method and physical method. Among them, BaCl2 method is the most widely used chemical sulfate radical removal method in industry, with simple process operation and good removal effect, but BaCl2 itself has strong toxicity, high storage condition requirements and high use cost. However, due to the large solubility product of calcium sulfate, the effect of CaCl2 method in removing sulfate radical is relatively poor compared with BaCl2 method. Due to the large energy consumption of removing sulfate radical, freezing method is rarely used in industry. Among physical methods, physical adsorption method is still in the research stage, membrane separation method has problems of membrane pollution, high energy consumption and high cost, and concentration polarization generated during operation is easy to cause scaling, so its application in the field of industrial wastewater treatment is limited.

[0004] Therefore, it is urgent to develop a method for removing high-concentration sulfate with simple operating conditions, low treatment cost and no secondary pollution for application in industrial wastewater treatment. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a composite seed crystal and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a method for preparing a composite seed crystal, the preparation method comprising the following steps: preparing a seed crystal carrier and a seed crystal separately, and then mixing the seed crystal carrier and the seed crystal, and calcining to obtain a composite seed crystal;

[0007] The preparation steps of the seed crystal carrier include: dissolving aluminate and sulfate in water to obtain a solution 1, adding silica sol to the solution 1 under stirring conditions, standing for aging, crystallizing at a constant temperature, separating a solid product, and drying to obtain the seed crystal carrier;

[0008] The preparation steps of the seed crystals include: dissolving Ca(NO3)2·4H2O in water to obtain solution 2, dissolving Al2(SO4)3·18H2O in water to obtain solution 3, mixing the solution 2 and the solution 3 for reaction, maintaining the pH at 11-12 during the reaction, separating the solid product after the reaction, and obtaining primary seed crystals after drying; adding nitric acid solution to the primary seed crystals to react to obtain the seed crystals.

[0009] The preparation method of the composite crystal seed provided by the present invention is to prepare a composite crystal seed with high efficiency inducing sulfate radical attachment precipitation by loading the crystal seed on a crystal seed carrier. The composite crystal seed utilizes sulfate radicals and calcium ions present in the water body, and based on the means of inducing destabilization precipitation of the supersaturated state solution, provides a site for the attachment of sulfate radical precipitation, and effectively reduces the reaction activation energy of sulfate radical precipitation crystallization, increases the reaction surface area, and finally can achieve the technical effect of high efficiency removal of sulfate radicals in the water body.

[0010] In some embodiments of the present invention, the aluminate includes one or more of KAlO2 and NaAlO2.

[0011] In some embodiments of the present invention, the sulfate includes one or more of MgSO4, K2SO4, and Na2SO4.

[0012] In some embodiments of the present invention, the AlO2 of the aluminate in the solution 1 - The concentration is 1.5-3 mol / L, for example, 2 mol / L, 2.3 mol / L, 2.6 mol / L, 2.9 mol / L, etc.

[0013] In some embodiments of the present invention, the sulfate SO4 in the solution 1 2- The concentration is 2-4 mol / L, for example 2.5 mol / L, 3 mol / L, 3.5 mol / L, etc.

[0014] In some embodiments of the present invention, the concentration of SiO2 in the silica sol is 0.25-0.3 mol / L, for example, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L, etc.

[0015] In some embodiments of the present invention, the molar ratio of the aluminate, sulfate and SiO2 is 6:(4-8):(1-1.2), for example 6:4:1, 6:5:1, 6:6:1.2, 6:7:1.1, 6:8:1, etc.

[0016] When the addition ratio of the aluminate, sulfate and SiO2 is within the scope of the present invention, a complete and stable carrier structure can be formed; when the addition ratio of the aluminate, sulfate and SiO2 is higher than the scope of the present invention, the base material silicon dioxide of the seed carrier is insufficient, which will lead to poor stability of the seed carrier; when the addition ratio of the aluminate, sulfate and SiO2 is lower than the scope of the present invention, the component combined with the seed crystal in the seed carrier is insufficient, which will weaken the effect of removing sulfate.

[0017] In some embodiments of the present invention, the silica sol is added dropwise.

[0018] In some embodiments of the present invention, the dropping rate of the silica sol is 1-2 mL / min, for example, 1.1 mL / min, 1.3 mL / min, 1.5 mL / min, 1.7 mL / min, 1.9 mL / min, etc.

[0019] The silica sol described in the present invention is a dispersion of nano-scale SiO2 in water. The silica sol can be used as the main component of the carrier to improve the strength and hardness of the material and enhance the durability of the material. The silica sol described in the present invention can be prepared by conventional technical means in the art, including but not limited to ion exchange method, one-step hydrolysis of silicon powder, electrolytic dialysis method, etc.

[0020] In some embodiments of the present invention, the stirring and aging temperature in the preparation of the seed carrier is 20-30° C., for example, 2.2 h, 2.4 h, 2.6 h, 2.8 h, etc.

[0021] In some embodiments of the present invention, the stirring time in the preparation of the seed carrier is 2 to 3 hours, for example, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, etc.

[0022] In some embodiments of the present invention, the aging time in the preparation of the seed crystal carrier is 10 to 12 hours, such as 10.5 hours, 11 hours, 11.5 hours, etc.

[0023] In some embodiments of the present invention, the stirring rate in the preparation of the seed carrier is 150-200 r / min, for example, 160 r / min, 170 r / min, 180 r / min, 190 r / min, etc.

[0024] If the stirring rate is too low, the reaction will be incomplete and a complete carrier structure cannot be formed. If the stirring rate is too high, the carrier structure will be destroyed and the preparation of the carrier cannot be achieved. Stirring within the rate range of the present invention can form a complete carrier structure under the premise of ensuring sufficient reaction.

[0025] In some embodiments of the present invention, the temperature of the isothermal crystallization is 90-100°C, for example, 91°C, 93°C, 95°C, 97°C, 99°C, etc.

[0026] In some embodiments of the present invention, the isothermal crystallization time is 6 to 8 hours, for example, 6.2 hours, 6.5 hours, 6.8 hours, 7 hours, 7.2 hours, 7.5 hours, 7.8 hours, etc.

[0027] In some embodiments of the present invention, the drying time of the solid product is 6 to 8 hours, for example, 6.5 hours, 7 hours, 7.5 hours, etc.

[0028] In some embodiments of the present invention, the drying temperature of the solid product is 80-100°C, such as 85°C, 90°C, 95°C, etc.

[0029] In some embodiments of the present invention, the step of preparing the seed carrier further comprises: washing the solid product before drying.

[0030] In the preparation of the seed crystal carrier of the present invention, the main purpose of washing the solid product is to remove impurities to prevent the impurities from affecting the subsequent preparation of the composite seed crystal. The requirement for washing is to wash until the pH of the solid product is 6.5-7.5, such as 6.6, 6.8, 7.0, 7.2, 7.4, etc.

[0031] In some embodiments of the present invention, the concentration of Ca(NO3)2·4H2O in the solution 2 is 1 to 1.2 mol / L, for example, 1.04 mol / L, 1.08 mol / L, 1.1 mol / L, 1.14 mol / L, 1.18 mol / L, etc.

[0032] In some embodiments of the present invention, the concentration of Al2(SO4)3·18H2O in the solution 3 is 0.3-0.4 mol / L, for example, 0.31 mol / L, 0.33 mol / L, 0.35 mol / L, 0.37 mol / L, 0.39 mol / L, etc.

[0033] In some embodiments of the present invention, the molar ratio of Ca(NO3)2·4H2O and Al2(SO4)3·18H2O is 1:(0.25-0.4), for example, 1:0.27, 1:0.3, 1:0.33, 1:0.35, 1:0.37, etc.

[0034] It should be noted that the crystal water in Ca(NO3)2·4H2O and Al2(SO4)3·18H2O in the present invention can be combined with other parts of the crystal through a specific bonding method to construct the three-dimensional structure of the entire crystal, which is beneficial to maintaining the overall stability and integrity of the crystal.

[0035] In some embodiments of the present invention, the reaction in the step of preparing the primary seed crystals includes: first reacting under stirring conditions and then reacting at rest.

[0036] In some embodiments of the present invention, the stirring time in the preparation of the primary seed crystals is 8 to 10 h, for example, 8.3 h, 8.5 h, 8.7 h, 9 h, 9.3 h, 9.5 h, 9.7 h, etc.

[0037] In some embodiments of the present invention, the stirring temperature in the preparation of the primary seed crystals is 35-45°C, for example, 36°C, 38°C, 40°C, 42°C, 44°C, etc.

[0038] In some embodiments of the present invention, the standing time in the preparation of the primary seed crystals is 2 to 3 hours, for example, 2.1 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.9 hours, etc.;

[0039] In some embodiments of the present invention, the standing temperature in the preparation of the primary seed crystals is 15-25°C, for example, 16°C, 18°C, 20°C, 22°C, 24°C, etc.

[0040] In some embodiments of the present invention, the drying time in the preparation of the seed crystal is 6 to 8 hours, such as 6.5 hours, 7 hours, 7.5 hours, etc.

[0041] In some embodiments of the present invention, the drying temperature in the preparation of the seed crystals is 80-100°C, such as 85°C, 90°C, 95°C, etc.

[0042] In some embodiments of the present invention, during the preparation of the seed crystal, the pH is maintained by adding an alkaline solution, and the alkaline solution may be a strong base with good solubility, including but not limited to one or more of NaOH and KOH. The present invention does not limit the concentration of the alkaline solution, as long as the pH is maintained in the range of 11 to 12.

[0043] In some embodiments of the present invention, the concentration of the nitric acid solution is 4-5 mol / L, for example, 4.1 mol / L, 4.3 mol / L, 4.5 mol / L, 4.7 mol / L, 4.9 mol / L, etc.

[0044] In some embodiments of the present invention, the solid-liquid ratio of the primary seed crystals to the nitric acid solution is 8 to 10 g / 100 ml, for example, 8 g / 100 ml, 9 g / 100 ml, 10 g / 100 ml, etc.

[0045] In some embodiments of the present invention, the reaction after adding the nitric acid solution is carried out under shaking and water bath conditions.

[0046] In some embodiments of the present invention, the reaction time after adding the nitric acid solution is 2 to 3 hours, for example, 2.1 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.9 hours, etc.

[0047] In some embodiments of the present invention, the temperature of the reaction after adding the nitric acid solution is 60-80°C, for example, 62°C, 65°C, 68°C, 70°C, 75°C, 78°C, etc.

[0048] In some embodiments of the present invention, the rotation speed of the shaking table is 240-300 r / min, for example, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, etc.

[0049] In some embodiments of the present invention, the seed crystal preparation step further includes: filtering, washing, and drying after the reaction between the primary seed crystal and the nitric acid solution is completed.

[0050] In some embodiments of the present invention, the mass ratio of the seed crystal carrier to the seed crystal is 1:0.8-1, for example, 1:0.85, 1:0.9, 1:0.95, etc.

[0051] In some embodiments of the present invention, the calcination temperature is 250-300°C, such as 260°C, 270°C, 280°C, 290°C, etc.

[0052] In some embodiments of the present invention, the calcination time is 150 to 180 min, for example, 155 min, 160 min, 165 min, 170 min, 175 min, etc.

[0053] In some embodiments of the present invention, the average particle size of the composite seed crystals is 150-250 μm, for example, 155 μm, 170 μm, 185 μm, 200 μm, 215 μm, 230 μm, 245 μm, etc.

[0054] In a second aspect, the present invention provides a composite seed crystal, which is prepared by the preparation method described in the first aspect.

[0055] The seed carrier of the present invention is a silicon-based carrier containing sulfate, and the loaded seed is a sulfate adsorption material containing calcium sulfate crystals. The composite seed provided by the present invention adopts a loading method to load the seed on the seed carrier, which is beneficial to improve the dispersibility of the seed and prevent the seed from reducing the reaction activity due to aggregation.

[0056] In a third aspect, the present invention provides an application of the composite crystal seed as described in the second aspect, wherein the composite crystal seed is used to remove sulfate ions in water.

[0057] The composite crystal seeds provided by the present invention are applied to the treatment of high-concentration sulfate wastewater. The core crystal granulation technology is used, sulfate and calcium ions existing in the water are utilized, and based on the means of inducing destabilization and precipitation of a supersaturated solution, the addition of the composite crystal seeds provides attachment sites for the precipitation of the original sulfate in the water, so that the sulfate and calcium ions coexisting in the water are destabilized to form precipitation, and on the other hand, the reaction activation energy is reduced through the crystallization process, the reaction surface area is increased, and a dense granulation body with a large particle size and good sedimentation performance can be formed, thereby achieving an efficient removal effect of sulfate in the water and improving water quality.

[0058] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0059] The composite crystal seeds prepared by the preparation method provided by the present invention can provide sites for the precipitation and attachment of sulfate radicals on the one hand, and can effectively reduce the reaction activation energy of the sulfate radical precipitation and crystallization process on the other hand, thereby increasing the reaction surface area; the composite crystal seeds can be applied to the removal of high-concentration sulfate radicals in wastewater, thereby significantly reducing the sulfate radical concentration; and the process cost is reduced, sludge is not generated, and there is no secondary pollution, thereby being suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0061] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0062] Figure 1 The XRD characterization diagram of the seed carrier, seed and composite seed described in Example 1 of the present invention;

[0063] Figure 2 FT-IR characterization diagram of the seed carrier, seed and composite seed described in Example 1 of the present invention;

[0064] Figure 3 This is a diagram showing the effect of the composite seed crystals described in Example 1 of the present invention on the removal of sulfate radicals in water;

[0065] Figure 4 This is a SEM characterization image of the composite seed nucleation granulation technology described in Example 1 of the present invention before the sulfate removal performance test;

[0066] Figure 5This is a SEM characterization image after the sulfate removal performance test of the composite seed nucleation granulation technology described in Example 1 of the present invention. DETAILED DESCRIPTION

[0067] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0068] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0069] Example 1

[0070] This embodiment provides a composite seed crystal, and the preparation steps are as follows:

[0071] Preparation of seed carrier: According to the molar ratio (as shown in Table 1), weigh 2mol / L NaAlO2 and 3mol / L Na2SO4, put them in a 1L stirring bucket, add deionized water, stir vigorously to completely dissolve them to obtain solution 1, after solution 1 is completely clarified, weigh 0.25mol / L silica sol as a silicon source and add it dropwise to solution 1 at a rate of 1mL / min, stir vigorously at 150r / min for 2h at 30℃, and age the synthetic liquid for 12h. Then transfer the aged synthetic liquid to the reactor, put it in a 100℃ constant temperature drying oven for constant temperature crystallization for 6h to obtain a precipitate, and finally use a centrifuge to repeatedly wash the precipitate until the pH is 6.5, and put the washed precipitate in a 90℃ constant temperature drying oven for 8h to prepare a seed carrier;

[0072] Preparation of seed crystals: According to the molar ratio (as shown in Table 1), 1 mol / L Ca(NO3)2·4H2O was weighed and dissolved in deionized water to obtain solution 2, and 0.3 mol / L Al2(SO4)3·18H2O was weighed and dissolved in deionized water to obtain solution 3. Solution 2 and solution 3 were transferred to the same flask, stirred at 35°C for 8 h to mix, and 0.1 mol / L NaOH was added to maintain the pH at 11.5. The mixture was allowed to stand at 25°C for 2 h, filtered, and dried at 100°C for 8 h to obtain primary seed crystals.

[0073] Weigh 8 g of primary seed crystals and put them into a conical flask, add 100 mL of 4 mol / L nitric acid solution, place the conical flask in a shaker, react in a water bath at a shaker speed of 240 r / min and a temperature of 80°C for 2 h, then filter, wash the filter cake and dry it at 40°C to obtain seed crystals.

[0074] According to the mass ratio of seed carrier: seed = 1:1, the seed carrier and the seed were placed in a calcination furnace at a temperature of 300° C. and calcined for 180 minutes to prepare a composite seed.

[0075] Example 2

[0076] This embodiment provides a composite seed crystal, and the preparation steps are as follows:

[0077] Preparation of seed carrier: According to the molar ratio (as shown in Table 1), weigh 1.5mol / L NaAlO2 and 4mol / L Na2SO4, put them in a 1L stirring bucket, add deionized water, stir vigorously to completely dissolve them to obtain solution 1, after solution 1 is completely clarified, weigh 0.3mol / L silica sol as a silicon source and add it dropwise to solution 1 at a rate of 1.5mL / min, stir vigorously at 200r / min for 3h at 20℃, and age the synthetic liquid for 10h. Then transfer the aged synthetic liquid to the reactor, put it in a 90℃ constant temperature drying oven for constant temperature crystallization for 8h to obtain a precipitate, and finally use a centrifuge to repeatedly wash the precipitate until the pH is 7, and put the washed precipitate in a 100℃ constant temperature drying oven to dry for 6h to prepare a seed carrier;

[0078] Preparation of seed crystals: According to the molar ratio (as shown in Table 1), 1.2 mol / L of Ca(NO3)2·4H2O was weighed and dissolved in deionized water to obtain solution 2, and 0.4 mol / L of Al2(SO4)3·18H2O was weighed and dissolved in deionized water to obtain solution 3. Solution 2 and solution 3 were transferred to the same flask, stirred at 45°C for 9 h to mix, and 0.1 mol / L NaOH was added to maintain the pH at 11. The mixture was allowed to stand at 15°C for 3 h, filtered, and dried at 80°C for 7 h to obtain primary seed crystals.

[0079] Weigh 9 g of primary seed crystals and put them into a conical flask, add 100 mL of 5 mol / L nitric acid solution, place the conical flask in a shaker, and react in a water bath at a shaker speed of 280 r / min and a temperature of 70°C for 2.5 hours, then filter and wash the filter cake, then dry it at 40°C to obtain seed crystals.

[0080] According to the mass ratio of seed carrier: seed = 1:0.8, the seed carrier and the seed were placed in a calcination furnace at a temperature of 280° C. and calcined for 150 minutes to prepare a composite seed.

[0081] Example 3

[0082] This embodiment provides a composite seed crystal, and the preparation steps are as follows:

[0083] Preparation of seed carrier: According to the molar ratio (as shown in Table 1), weigh 3 mol / L NaAlO2 and 2 mol / L Na2SO4, put them in a 1L stirring bucket, add deionized water, stir vigorously to completely dissolve them to obtain solution 1, after solution 1 is completely clarified, weigh 0.28 mol / L silica sol as a silicon source and add it dropwise to solution 1 at a rate of 2 mL / min, stir vigorously at 180 r / min for 2.5 hours at 35°C, and age the synthetic liquid for 11 hours. Then transfer the aged synthetic liquid to the reactor, put it in a 95°C constant temperature drying oven for constant temperature crystallization for 7 hours to obtain a precipitate, and finally use a centrifuge to repeatedly wash the precipitate until the pH is 7.5, and put the washed precipitate in a 80°C constant temperature drying oven to dry for 7 hours to prepare a seed carrier;

[0084] Preparation of seed crystals: According to the molar ratio (as shown in Table 1), 1.1 mol / L Ca(NO3)2·4H2O was weighed and dissolved in deionized water to obtain solution 2, and 0.35 mol / L Al2(SO4)3·18H2O was weighed and dissolved in deionized water to obtain solution 3. Solution 2 and solution 3 were transferred to the same flask, stirred at 40°C for 10 h to mix, and 0.1 mol / L NaOH was added to maintain the pH at 12. The mixture was allowed to stand at 20°C for 2.5 h, filtered, and dried at 90°C for 6 h to obtain primary seed crystals.

[0085] Weigh 10 g of primary seed crystals and put them into a conical flask, add 100 mL of 4.5 mol / L nitric acid solution, place the conical flask in a shaker, and react in a water bath at a shaker speed of 300 r / min and a temperature of 60°C for 3 hours, then filter and wash the filter cake, then dry it at 40°C to obtain seed crystals.

[0086] According to the mass ratio of seed carrier: seed = 1:0.9, the seed carrier and the seed were placed in a calcination furnace at a temperature of 250° C. and calcined for 170 minutes to prepare a composite seed.

[0087] Table 1 Molar ratio of substances in the composite seed preparation process

[0088] Molar Ratio <![CDATA[NaAlO2:Na2SO4:SiO2]]> <![CDATA[Ca(NO3)2·4H2O:Al2(SO4)3·18H2O]]> Example 1 6:5:1 1:0.25 Example 2 6:8:1.2 1:0.3 Example 3 6:6:1 1:0.4

[0089] Performance Testing

[0090] 1. XRD and FT-IR characterization

[0091] The seed carrier, seed crystal and composite seed crystal prepared in Example 1 were characterized by XRD and FT-IR, respectively. The test results are as follows: Figure 1 and Figure 2 shown.

[0092] Figure 1This is a comparison of the XRD patterns of the seed carrier, seed crystal and composite seed crystal prepared in Example 1 of the present disclosure. Figure 1 It can be seen that for the composite seed, the characteristic peaks at 14.5° and 29.7° correspond to the characteristic peaks of the seed carrier, and the characteristic peaks at 44.7°, 66.9° and 82.3° correspond to the characteristic peaks of the seed. The above results show that the characteristic peaks of the composite seed correspond to the characteristic peaks of the seed and the seed carrier, which indicates that the seed has been successfully loaded on the surface of the seed carrier.

[0093] Figure 2 This is a FT-IR comparison chart of the seed carrier, seed and composite seed prepared in Example 1 of the present disclosure. Figure 2 It can be seen that the composite seed has a peak at 2910 cm -1 and 2861cm -1 There are characteristic peaks at 3420 cm -1 、1656cm -1 and 1085cm -1 There are obvious characteristic peaks appearing at the corresponding peak positions in the corresponding composite seeds, which indicates that the seeds have been successfully loaded on the surface of the seed carrier. The FT-IR results and XRD results confirm each other.

[0094] 2. Performance test of sulfate removal by nuclear crystal granulation technology

[0095] Wastewater containing high concentration of sulfate (80mM, 120mM, 160mM, respectively) was adjusted to pH 7 to obtain treated raw water. The treated raw water entered a nuclear crystal granulation reactor, and the seeds, composite seeds and garnet seeds prepared in Example 1 were added to the reactor respectively, the dosage of each seed was 25% of the reactor volume, the hourly flow rate of the inlet water was 15 times the volume of the reactor, and when the seeds or composite seeds were in a fluidized state, a crystallizing agent calcium chloride with a concentration of 9000ppm was added, and the flow rate of the crystallizing agent was 10% of the raw water flow rate, inducing sulfate ions in the water to precipitate on the surface of the seeds or the composite seeds, measuring the sulfate concentration and turbidity of the effluent, and taking the granules after the reaction to measure the particle size.

[0096] The results of the composite seed prepared in Example 1 are as follows:

[0097] Figure 3 This is a graph showing the removal effect of the composite seed crystals prepared in Example 1 of the present disclosure on sulfate radicals in water (the bar graph is turbidity, and the line graph is sulfate radical removal rate). Figure 3It can be known that under the enrichment effect of sulfate radical on the surface of composite crystal seeds, sulfate radical forms a local supersaturated state on the surface of composite crystal seeds, and finally adheres and precipitates on the surface of crystal seeds in the form of calcium sulfate. After nuclear crystal granulation reaction treatment, in the wastewater with an initial sulfate radical concentration of 80mM, the effluent sulfate radical concentration drops to less than 4000mg / L, the removal rate of sulfate radical is about 50%, and the turbidity is about 8NTU; in the wastewater with an initial sulfate radical concentration of 120mM, the effluent sulfate radical concentration drops to less than 5000mg / L, the removal rate of sulfate radical is about 60%, and the turbidity is about 7NTU; in the wastewater with an initial sulfate radical concentration of 160mM, the effluent sulfate radical concentration drops to less than 6000mg / L, the removal rate of sulfate radical is about 60%, and the turbidity is about 6NTU, indicating that the composite crystal seeds prepared by the present application can effectively remove sulfate radical in wastewater, and the low turbidity of the effluent indicates that sulfate radical forms a precipitate attached to the crystal seeds to form a granulation body, and the composite crystal seeds prepared by the present application are conducive to the further treatment of subsequent wastewater and environmental friendliness.

[0098] The results of the seeds prepared in Example 1:

[0099] In the wastewater with an initial sulfate concentration of 80 mM, the effluent sulfate concentration dropped to about 5000 mg / L, the sulfate removal rate was about 35%, and the turbidity was about 40 NTU; in the wastewater with an initial sulfate concentration of 120 mM, the effluent sulfate concentration dropped to about 7500 mg / L, the sulfate removal rate was about 35%, and the turbidity was about 70 NTU; in the wastewater with an initial sulfate concentration of 160 mM, the effluent sulfate concentration dropped to about 9000 mg / L, the sulfate removal rate was about 40%, and the turbidity was about 80 NTU, indicating that the seed crystals prepared in Example 1 are difficult to effectively remove sulfate in the wastewater, and the high turbidity of the effluent indicates that the sulfate precipitate is difficult to adhere to the seed crystals prepared in Example 1.

[0100] Results of garnet seeds:

[0101] In the wastewater with an initial sulfate concentration of 80 mM, the effluent sulfate concentration dropped to about 6000 mg / L, the sulfate removal rate was about 20%, and the turbidity was about 50 NTU; in the wastewater with an initial sulfate concentration of 120 mM, the effluent sulfate concentration dropped to about 8500 mg / L, the sulfate removal rate was about 25%, and the turbidity was about 80 NTU; in the wastewater with an initial sulfate concentration of 160 mM, the effluent sulfate concentration dropped to about 10000 mg / L, the sulfate removal rate was about 30%, and the turbidity was about 100 NTU, indicating that garnet seeds are difficult to effectively remove sulfate in the wastewater, and the high turbidity of the effluent indicates that the sulfate precipitate is not attached to the garnet.

[0102] From the above results, it can be seen that the composite crystal seeds prepared by the present invention have a significantly better treatment effect on sulfate in wastewater than the crystal seeds without a crystal carrier and the ordinary garnet crystal seeds.

[0103] 3. SEM Characterization

[0104] The morphology of the composite seed and granulation body in Example 1 was characterized by SEM. The test results are as follows: Figure 4 and Figure 5 shown.

[0105] Figure 4 and Figure 5 The SEM images are respectively of the composite seed crystal prepared in Example 1 of the present disclosure before and after the sulfate removal performance test using the core crystal granulation technology. Figure 4 It can be seen that the average particle size of the composite seed before the performance test is 215 μm, and the shape is a hexagram. Figure 5 It can be seen that after the nuclear crystal granulation performance test, the calcium sulfate precipitate adheres to the surface of the composite seed crystal, the average particle size increases to 650μm, and the shape is uniformly distributed dense granules, indicating that the composite seed crystal successfully forms a dense granulation body after reaction.

[0106] In summary, the composite crystal seeds prepared by the preparation method of the composite crystal seeds provided in the present invention have high reaction activity and are applied to the treatment of high-concentration sulfate ions in wastewater. The operating conditions are simple, and the sulfate ions and calcium ions present in the water body can be utilized to efficiently remove sulfate ions in the wastewater based on the means of inducing destabilization and precipitation of the supersaturated solution. The treatment cost is low and there is no secondary pollution, so the composite crystal seeds are suitable for industrial promotion.

[0107] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0108] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a composite seed crystal, characterized in that: The preparation method comprises the following steps: preparing a seed crystal carrier and a seed crystal separately, and then mixing the seed crystal carrier and the seed crystal, and calcining to obtain a composite seed crystal; The preparation steps of the seed crystal carrier include: dissolving aluminate and sulfate in water to obtain a solution 1, adding silica sol to the solution 1 under stirring conditions, standing for aging, crystallizing at a constant temperature, separating a solid product, and drying to obtain the seed crystal carrier; The preparation steps of the seed crystals include: dissolving Ca(NO3)2·4H2O in water to obtain solution 2, dissolving Al2(SO4)3·18H2O in water to obtain solution 3, mixing the solution 2 and the solution 3 for reaction, maintaining the pH at 11-12 during the reaction, separating the solid product after the reaction, and obtaining primary seed crystals after drying; adding nitric acid solution to the primary seed crystals to react to obtain the seed crystals.

2. The preparation method according to claim 1, characterized in that: The metaaluminate includes one or more of KAlO2 and NaAlO2; Preferably, the sulfate includes one or more of MgSO4, K2SO4, and Na2SO4.

3. The preparation method according to claim 1 or 2, characterized in that: The AlO2 of the aluminate in solution 1 - The concentration is 1.5~3mol / L; Preferably, the sulfate SO4 in the solution 1 2- The concentration is 2~4mol / L ; Preferably, the concentration of SiO2 in the silica sol is 0.25-0.3 mol / L; Preferably, the molar ratio of the aluminate, sulfate and SiO2 is 6:(4-8):(1-1.2).

4. The preparation method according to any one of claims 1 to 3, characterized in that The silica sol is added dropwise; Preferably, the silica sol is added at a rate of 1 to 2 mL / min; Preferably, the stirring and aging temperature in the preparation of the seed carrier is 20 to 30°C; Preferably, the stirring time in the preparation of the seed carrier is 2 to 3 hours; Preferably, the aging time in the preparation of the seed carrier is 10 to 12 hours; Preferably, the stirring rate in the preparation of the seed carrier is 150 to 200 r / min; Preferably, the temperature of the isothermal crystallization is 90-100°C; Preferably, the isothermal crystallization time is 6 to 8 hours; Preferably, the step of preparing the seed carrier further comprises: washing the solid product before drying.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The concentration of Ca(NO3)2·4H2O in the solution 2 is 1 to 1.2 mol / L; Preferably, the concentration of Al2(SO4)3·18H2O in the solution 3 is 0.3-0.4 mol / L; Preferably, the molar ratio of Ca(NO3)2·4H2O to Al2(SO4)3·18H2O is 1:(0.25-0.4).

6. The preparation method according to any one of claims 1 to 5, characterized in that: The reaction in the step of preparing the primary seed crystals includes: first reacting under stirring conditions and then reacting at rest; Preferably, the stirring time in the preparation of the primary seed crystals is 8 to 10 hours; Preferably, the stirring temperature in the preparation of the primary seed crystals is 35 to 45°C; Preferably, the standing time in the preparation of the primary seed crystal is 2 to 3 hours; Preferably, the standing temperature in the preparation of the primary seed crystals is 15-25°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The concentration of the nitric acid solution is 4-5 mol / L; Preferably, the solid-liquid ratio of the primary seed crystals to the nitric acid solution is 8 to 10 g / 100 ml; Preferably, the reaction after adding the nitric acid solution is carried out under shaking and water bath conditions; Preferably, the reaction time after adding the nitric acid solution is 2 to 3 hours; Preferably, the temperature of the reaction after adding the nitric acid solution is 60 to 80°C; Preferably, the rotation speed of the shaking table is 240-300 r / min.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The mass ratio of the seed carrier to the seed is 1:0.8-1; Preferably, the calcination temperature is 250-300°C; Preferably, the calcination time is 150 to 180 minutes; Preferably, the D50 particle size of the composite seed crystal is 150-250 μm.

9. A composite seed crystal, characterized in that: The composite seed crystal is prepared by the preparation method according to any one of claims 1 to 8.

10. A use of the composite seed crystal according to claim 9, characterized in that: The composite seed crystal is used for removing sulfate radicals in water.